2005
DOI: 10.1074/jbc.m509497200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Inhibits Heat-induced Apoptosis Upstream of Mitochondria by Preventing Bax Translocation

Abstract: Hsp70 overexpression can protect cells from stress-induced apoptosis. Our previous observation that Hsp70 inhibits cytochrome c release in heat-stressed cells led us to examine events occurring upstream of mitochondrial disruption. In this study we examined the effects of heat shock on the proapoptotic Bcl-2 family member Bax because of its central role in regulating cytochrome c release in stressed cells. We found that heat shock caused a conformational change in Bax that leads to its translocation to mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
299
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(321 citation statements)
references
References 67 publications
(85 reference statements)
17
299
0
5
Order By: Relevance
“…A recent report suggests that inhibition of bax translocation to mitochondria by HSP70 is the crucial factor in the cellular decision to either trigger or suppress apoptosis. 25 We have focused on the pro-and anti-apoptotic bcl-2 family members because of their central role in regulating cytochrome c release in stressed cells. We have found that sorbitol treatment increased expression of the bax protein while decreasing the expression of bcl-2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that inhibition of bax translocation to mitochondria by HSP70 is the crucial factor in the cellular decision to either trigger or suppress apoptosis. 25 We have focused on the pro-and anti-apoptotic bcl-2 family members because of their central role in regulating cytochrome c release in stressed cells. We have found that sorbitol treatment increased expression of the bax protein while decreasing the expression of bcl-2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…finding, as an antiapoptotic role for this protein has been recently described (Stankiewicz et al, 2005). Some common genes for both concentrations of docetaxel included DCT, TYR, TYRP1 and MAF.…”
Section: Molecular Profiling Of Docetaxel Cytotoxicity H Hernández-vamentioning
confidence: 82%
“…The protection conferred by HSPs is not limited to these "chaperone" activities; HSPs also inhibit lipid peroxidation and oxidative damage to DNA (Park et al 1998;Su et al 1999;Martindale and Holbrook 2002). In addition, HSPs have been shown to inhibit multiple pro-apoptotic signaling events (Jaattela et al 1998;Beere et al 2000;Pandey et al 2000a, b;Concannon et al 2001Concannon et al , 2003Tsuchiya et al 2003;Stankiewicz et al 2005;Rodina et al 2007;Jiang et al 2009;Evans et al 2010;Pasupuleti et al 2010). HO-1 is a heat shock-inducible protein that lacks intrinsic chaperone activity; however, it inhibits oxidative stress, inflammation, and apoptosis in multiple tissue types (Kirkby and Adin 2006;Ryter et al 2006;Gozzelino et al 2010;Paine et al 2010;Blancou et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced HSP70 inhibits apoptotic cell death in a large number of systems. HSP70 inhibits multiple pro-apoptotic signals, including oligomerization of Bax, release of both cytochrome c and second mitochondria-derived activator of caspases (Smac) from mitochondria, formation of a functional apoptosome, and even cell death subsequent to caspase 3 activation (Jaattela et al 1998;Beere et al 2000;Tsuchiya et al 2003;Stankiewicz et al 2005;Jiang et al 2009;Evans et al 2010). Moreover, HSP70 inhibits aminoglycosideinduced hair cell death in vitro and hearing loss in vivo (Taleb et al 2008(Taleb et al , 2009May et al 2013).…”
Section: Introductionmentioning
confidence: 99%